배추 뿌리혹병의 효율적인 저항성 검정법 확립 - 이수민(Soo Min Lee); 정희수(Hee Soo Jung); 김헌(Hun Kim); 김흥태(Heung Tae Kim); 최경자(Gyung Ja Choi) (Sigmulbyeong yeon'gu, 2024)
Clubroot caused by Plasmodiophora brassicae is an important disease of crucifer crops worldwide. This study aimed to establish an efficient screening method to determine resistant cultivars of Chinese cabbage against P. brassicae. To do this, we investigated the virulence of seven P. brassicae isolates using seedlings of susceptible Chinese cabbage cultivar. The isolates exhibited different virulence in the plants and were divided into three groups based on their virulence. When we explored the disease occurrence in Chinese cabbage seedlings according to photoperiod after inoculation of P. brassicae and incubation temperature, the plants with all-day light showed higher disease severity than seedlings cultivated under 14 hr of light a day. The occurrence of clubroot disease was most severe at 25℃, followed by 20℃ and 18℃, but the fresh weight of clubroot of the seedlings cultivated at 20℃ was the highest, followed by plants grown at 25℃ and 18℃. When the seedlings of two commercial resistant cultivars were inoculated with the mixed spore suspensions of two different pathotype isolates of P. brassicae, disease severity increased as the spore concentration of the susceptible P. brassicae isolate among the two strains increased, suggesting that the clubroot development by different pathotype isolates was independent and not influenced by each other. Taken together, our results provide a faster and more accurate screening methods to determine the resistance of Chinese cabbage against P. brassicae. Plasmodiophora brassicae에 의해 발생하는 배추 뿌리혹병은 전 세계적으로 경제적 손실이 큰 식물병이다. 본 연구는 뿌리혹병 저항성 배추 품종 개발을 위한 저항성 검정법을 확립하기 위해 수행되었다. 7개의 P. brassicae 균주는 감수성 배추 품종에서 서로 다른 병원력을 보였으며, 병원력에 따라 3개 그룹으로 나눌 수 있었다. 뿌리혹병균 접종 후 재배 온도와 광 처리시간에 따른 뿌리혹병 발생은 실험한 모든 재배 온도에서 하루에 14시간 광을 처리하는 것보다 하루 종일 광을 조사한 처리구에서 뿌리혹병 발생이 많았다. 그리고 재배 온도에 따른 뿌리혹병 발생은 25℃, 20℃, 18℃ 순으로 많았지만, 뿌리혹의 무게는 20℃에서 가장 높았으며 그 다음은 25℃, 18℃ 순으로 높았다. 또한 서로 다른 pathotype의 두 균주를 혼합하여 저항성 배추 품종에 접종하면, 두 균주 중 감수성 관계의 뿌리혹병균의 포자 농도 증가에 따라 뿌리혹병 발생이 증가하였다. 즉, 다른 pathotype 균주들의 뿌리혹병 발생은 서로에게 영향을 받지 않고 독립적이었다. 이들 결과로부터 보다 신속하고 정확한 배추 뿌리혹병 저항성 검정법을 확립할 수 있었다.